The Effect of Changes In Price Level, Product Quality, Quality Of Service On Purchase Decisions In Ud. Ghoni Jati Jaya - Nurrochmah, Laili; Nur Tasya; Noor Iffatin Nadhifah; Sumarni (Publisher Cv. Inara, 2022)
This study was to determine the effect of changes in price levels, product quality, and service quality affect purchasing decisions at UD. Ghoni Jati Jaya, and to find out which variables have the most influence on purchasing decisions. This research is quantitative. Researchers will describe the situation in the field and how consumers make purchasing decisions. The population in this study are all people who make purchases at UD. Ghoni Jati Jaya. The sample in this study used incidental random sampling method. To determine the size of the sample that will be used in this study, the slovin approach formula is used with a sample of 30 respondents because consumers are UD. Ghoni Jati Jaya is predicted to take 350 per year from 2014 to 2020. The analytical tool used is the research instrument test, namely the multiple regression linear test and assisted by SPSS. In this study, attempts to analyze the independent variable (X) in this case is the independent variable that influences purchasing decisions, the independent variables include the price variable, product quality variable, and service quality variable. After everything is fulfilled, the last step is to do a multiple regression linear test. Variables of changes in price level, product quality, service quality are equal to zero or unchanged, then the Y value or purchase decision is 8.815. or it can be said that the three variables including changes in price levels, product quality, service quality have a joint effect of about 88.1% on purchasing decisions. The results of the analysis that the variables of changes in price levels, product quality, and service quality have a significant effect on purchasing decisions at UD. Ghoni Jati Jaya